The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1051/e3sconf/202122707001
|View full text |Cite
|
Sign up to set email alerts
|

Wheat harvesting by combine with GPS receiver and grain sensor

Abstract: This research describes the result of study and analyze the working process of the harvester combine with GPS receiver and grain level sensor in wheat harvesting. GPS receiver and grain level sensor showed that the combine harvester was working with what level of velocity in the real time regime and how much grain was being uploaded into grain tank. According to results when the yield increased from 2.62 t/ha to 6.22 t/ha, because of decreasing the work-velocity of the combine harvester, the work efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…In-field variability was notably high when recorded with the Among various factors causing this variability, the key factors could be rice germination, variations in harvester speed, cutter bar height and reel index, especially during setting up the machine, land slope and the size of field. Furthermore, previous researchers have also conformed the final yield data from combine harvester using the corresponding satellite images from a vegetation season, and have concluded that the former can be used to predict yield and to assess site-specific zone productivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-field variability was notably high when recorded with the Among various factors causing this variability, the key factors could be rice germination, variations in harvester speed, cutter bar height and reel index, especially during setting up the machine, land slope and the size of field. Furthermore, previous researchers have also conformed the final yield data from combine harvester using the corresponding satellite images from a vegetation season, and have concluded that the former can be used to predict yield and to assess site-specific zone productivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…For yield-based custom charges, the tariff negotiation between the service provider and the farmer would have been on the basis of simple average (based on few data points on the field); however, with the use of precision grain yield meter, now a weighted average yield value could be used, making it more closely represent the field variability. Generally, when the moisture of the cereal decreases, the combine work efficiency increases, however, the rate of grain loss in the header rises too [22]. the maximum yield with an average grain flow rate range of 6.36 t ha −1 and 22.35% moisture content.…”
Section: Yield Range and Moisture Content Mappingmentioning
confidence: 99%
“…According to [12], a reasonable amount of grain losses should not reach a maximum of 3% of the total crop yield. Reference [13] reported a grain loss of 5.3 percent in the header combine harvester, exceeding the minimum limitations. As a result, more studies will be required to find characteristics and operating conditions that minimize grain loss and combine harvester loss.…”
Section: Introductionmentioning
confidence: 95%
“…In Uzbekistan, coarse and concentrated feed is obtained mainly from wheat, soybean, corn and safflower [1][2][3]. Wheat and corn grains, as well as corn cobs after grinding, are used in concentrated feed, and wheat straw and corn stalks after harvesting are used in roughage [4][5][6]. Because roughage is the most important source of feed protein for livestock [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%